How Sustainable is the Silk Weaving Agroindustry? Evidence from Wajo Regency, South Sulawesi, Using Multi-Dimensional Scaling - Suratmi; Silvana Maulidah; Asihing Kustanti; Farida Rahayu; Anirut Pipatprapa (Jurnal Penelitian Pendidikan IPA, 2026)
This study evaluates the sustainability level of the silk weaving agroindustry in Wajo Regency, South Sulawesi, using a Multi-Dimensional Scaling (MDS) approach across four dimensions: economic, social, environmental, and resource based. Data were collected from 86 silk weaving agroindustry units through surveys and structured interviews. The results show that the overall sustainability status is classified as moderately sustainable, with sustainability index values of 72% (economic), 68% (resource), 64% (social), and 53% (environmental). The economic dimension demonstrates the strongest performance, reflecting relatively stable profitability and market accessibility, while the environmental dimension exhibits the lowest score, indicating weaknesses in waste management practices, the adoption of environmentally friendly materials, and environmental standards. These findings highlight environmental management as the main leverage point for improving overall sustainability. This study contributes to applied sustainability science by providing a quantitative, multidimensional assessment framework for traditional agroindustries and offers empirical evidence to support sustainability-oriented policy formulation and the strategic development of local silk weaving enterprises.